2013
DOI: 10.2478/raon-2013-0006
|View full text |Cite
|
Sign up to set email alerts
|

The value of the sagittal-oblique MRI technique for injuries of the anterior cruciate ligament in the knee

Abstract: BackgroundComplete rupture of the anterior cruciate ligament (ACL) does not represent a diagnostic problem for the standard magnetic resonance (MR) protocol of the knee. Lower accuracy of the standard MR protocol for partial rupture of the ACL can be improved by using additional, dedicated MR techniques. The study goal was to draw a comparison between sagittal-oblique MR technique of ACL imaging versus flexion MR technique of ACL imaging and, versus ACL imaging obtained with standard MR protocol of the knee.Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Moreover, they found that sagittal-oblique images require a shorter scan time compared to the flexion technique due to a higher number of MRI slices that show the whole course of the ACL. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they found that sagittal-oblique images require a shorter scan time compared to the flexion technique due to a higher number of MRI slices that show the whole course of the ACL. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…Recent progress in MRI techniques such as sagittaloblique technique and 3D fast spin echo may make it possible to identify the remnant ACL fibers because they can depict a partial ACL tear, 13,14 but they are not available in every institute. By standard MRI, complete ACL tears can be detected but there may be some difficulty in identifying remnant ACL 15 .…”
Section: Discussionmentioning
confidence: 99%
“…13). Additionally, dedicated MR protocols, including imaging the knee in a slightly flexed position or acquiring images in a sagittal oblique plane, can improve the diagnostic yield of partial tears [37,38]. When the knee is in flexion, there is improved accuracy secondary to the loss of volume averaging in the intercondylar notch.…”
Section: Cruciate Ligamentsmentioning
confidence: 99%